Disability discrimination in education and the defence of unjustifiable hardship - Waldeck, Elizabeth; Guthrie, Rob (School of Business Law & Taxation, Curtin Business School, 2004)
The Disability Discrimination Act 1992 (Cth) (the ‘DDA’) provides protection for the rights of people with disabilities in Australia in many facets of everyday life. This paper examines the DDA in relation to the prevention of discrimination in the area of education. This is of relevance to tertiary institutions such as universities, given that de-institutionalisation and mainstreaming over the last decade particularly has resulted in many more disabled people seeking to continue their studies at the tertiary level.The DDA prevents educational institutions from discriminating against a student on the grounds of the student’s disability in relation to admission and access to the institution and its services and facilities. However, the DDA also provides that it is not unlawful to discriminate in relation to these matters if the disabled student’s requirements are such that an unjustifiable hardship would be imposed upon the educational institution.Over the last twelve years, the courts have decided individual complaints consistent with the broad principles established by the DDA. Particularly relevant is the recent case of Purvis v State of New South Wales (Department of Education and Training) [2003] HCA 62, which has tested the boundaries of the DDA with respect to the definition of “disability”, the “appropriate comparator” issue and the provision by the educational institution of “reasonable accommodations”. The cases of Hills Grammar School v HREOC and Purvis discuss the unjustifiable hardship defence with the Hills Grammar School case particularly, providing a detailed determination of what constitutes the defence for the purposes of the DDA. Legislative amendments to the DDA as a result of a recent review undertaken by the Productivity Commission, in addition to the introduction of new education standards, have clarified the obligations imposed upon educational institutions with regard to disabled students. Educational institutions must take those steps necessary to satisfy the requirements of the DDA, thus avoiding claims of unlawful discrimination being made against them.